Multi Rate Output Feedback control of Doubly-fed Induction Motor - Biradar, Ravi K; Sarwadnya, R. V (International Journal of Computer Sciences and Engineering, 2025)
The problem of output feedback control of doubly fed induction motor (DFIM) is considered in this paper. In particular the technique of multirate output feedback (MROF) has been employed. The challenge in control of DFIM is the nonlinear nature of torque and speed dynamics which prevents direct application of MROF techniques. We have proposed a novel strategy to achieve the torque and speed tracking via state reference tracking. The linear equations of doubly fed induction motor are utilized for application of MROF and the state reference commands are computed from torque and speed reference commands separately. The proposed output feedback controller is shown to be tracking given torque and speed commands